Characterization of a Non-Canonical Signal Peptidase Cleavage Site in a Replication Protein from Tomato Ringspot Virus - Wei, Ting (PLoS One, 2016)
The NTB-VPg polyprotein from tomato ringspot virus is an integral membrane replication protein associated with endoplasmic reticulum membranes. A signal peptidase (SPase) cleavage was previously detected in the C-terminal region of NTB-VPg downstream of a 14 amino acid (aa)-long hydrophobic region (termed TM2). However, the exact location of the cleavage site was not determined. Using in vitro translation assays, we show that the SPase cleavage site is conserved in the NTB-VPg protein from various ToRSV isolates, although the rate of cleavage varies from one isolate to another. Systematic site-directed mutagenesis of the NTB-VPg SPase cleavage sites of two ToRSV isolates allowed the identification of sequences that affect cleavage efficiency. We also present evidence that SPase cleavage in the ToRSV-Rasp2 isolate occurs within a GAAGG sequence likely after the AAG (GAAG/G). Mutation of a downstream MAAV sequence to AAAV resulted in SPase cleavage at both the natural GAAG/G and the mutated AAA/V sequences. Given that there is a distance of seven aa between the two cleavage sites, this indicates that there is flexibility in the positioning of the cleavage sites relative to the inner surface of the membrane and the SPase active site. SPase cleavage sites are typically located 3–7 aa downstream of the hydrophobic region. However, the NTB-VPg GAAG/G cleavage site is located 17 aa downstream of the TM2 hydrophobic region, highlighting unusual features of the NTB-VPg SPase cleavage site. A putative 11 aa-long amphipathic helix was identified immediately downstream of the TM2 region and five aa upstream of the GAAG/G cleavage site. Based on these results, we present an updated topology model in which the hydrophobic and amphipathic domains form a long tilted helix or a bent helix in the membrane lipid bilayer, with the downstream cleavage site(s) oriented parallel to the membrane inner surface.